Design, fabrication and characterization of a pure uniaxial microloading system for biologic testing. Issue 4 (April 2016) - King, Jonathan D.; York, Spencer L.; Saunders, Marnie M.
Abstract: The field of mechanobiology aims to understand the role the mechanical environment plays in directing cell and tissue development, function and disease. The empirical aspect of the field requires the development of accurate, reproducible and reliable loading platforms that can apply microprecision mechanical load. In this study we designed, fabricated and characterized a pure uniaxial loading platform capable of testing small synthetic and organic specimens along a horizontal axis. The major motivation for platform development was in stimulating bone cells seeded on elastomeric substrates and soft tissue loading. The biological uses required the development of culturing fixtures and environmental chamber. The device utilizes commercial microactuators, load cells and a rail/carriage block system. Following fabrication, acceptable performance was verified by suture tensile testing. Highlights: A device for pure uniaxial microloading of biologic samples was designed. Design restrictions included low cost, biologic compatibility and reliability. This device was verified by comparison to an existing device. This low costs device replaces the need of standard cost prohibitive devices.